Building strategy from the middle : reconceptualizing strategy process - Floyd, Steven W., 1950- (Foundations for Organizational Science Ser., 2000)
This title presents a provocative new take on strategy formulation and execution - namely that strategic business leadership occurs not only at the top, but at all levels of the organisation.